TEACHING-LEARNING PROCESS SCHOOLS IN HEALTH: THEORETICAL REFLECTIONS (Fiep Bulletin - online, 2013)
This study argues the teaching and learning process, establishing the relations between development, learning and education in the context of the interactionists theories. It reflects, still, on the aspects of the learning environment that facilitates the professor to go beyond the condition of transmitter of the informations to the condition of the person who facilitates, guides and stimulates the learning. At this time of curricular changes movement and the proposal of Problem-Based Learning (PBL) the training of new health workers demands conceptual and practical changes of the professors, having in the center the student. To play this new role as the person who facilitates and the “arbitrator of learning” educator, it is necessary that the professor understands how does it give the process of construction of knowledge, considering the student as social-historical subject, producer of his own knowledge.
Keywords: knowledge; Teach and learning; Problem-Based Learning; Constructivism